Effects of markedness in gender processing in Italian as a heritage language: A speed accuracy tradeoff - Di Pisa, Grazia; Kubota, Maki; Rothman, Jason; Marinis, Theodoros (Frontiers in Psychology, 2022)
This study examined potential sources of grammatical gender variability in heritage speakers (HSs) of Italian with a focus on morphological markedness. Fifty-four adult Italian HSs living in Germany and 40 homeland Italian speakers completed an online Self-Paced Reading Task and an offline Grammaticality Judgement Task. Both tasks involved sentences with grammatical and ungrammatical noun-adjective agreement, manipulating markedness. In grammatical sentences, both groups showed a markedness effect: shorter reading times (RTs) and higher accuracy for sentences containing masculine nouns as compared to sentences with feminine nouns. In ungrammatical sentences, although both groups were sensitive to ungrammaticality, only HSs showed a markedness effect, that is, they had significantly longer RTs and higher accuracy when violations were realized on feminine adjectives. Proficiency in the HL was a significant predictor of accuracy and RTs at the individual level. Taken together, results indicate that HSs acquire and process gender in a qualitatively similar way to homeland native speakers. However, RT evidence seems to suggest that at least under particular experimental methods, markedness considerations are more prevalent for HSs resulting in a speed-accuracy tradeoff.